Comparative Study of Astaxanthin, Cholesterol, Fatty Acid Profiles, and Quality Indices Between Shrimp Oil Extracted From Hepatopancreas and Cephalothorax - Raju, Navaneethan; Gulzar, Saqib; Buamard, Natchaphol; Ma, Lukai; Ying, Xiaoguo; Zhang, Bin; Benjakul, Soottawat (Frontiers in Nutrition, 2021)
Shrimp oil from two different portions of Pacific white shrimp including cephalothorax and hepatopancreas was extracted using the mixture of hexane/isopropanol (1:1). The extracted oils from the cephalothorax (CPO) and hepatopancreas (HPO) were characterized for astaxanthin content, cholesterol levels, and fatty acid profiles. Nutrition indices of CPO and HPO were also compared. CPO had lower extraction yield (3.2 ± 0.1%, wet weight basis) than HPO (11.1 ± 0.5%, wet weight basis). High-performance liquid chromatography results indicated that the astaxanthin content in HPO was higher, compared to that of CPO. Nevertheless, the cholesterol level in HPO was 70% lower than that of CPO. Fatty acid profiles of HPO and CPO demonstrated that the polyunsaturated fatty acid (PUFA) content in HPO was higher than that of CPO. The amount of docosahexaenoic acid in the former was 2 times higher than that of the latter. HPO contained 42.76 ± 0.36% PUFA, whereas PUFA content of CPO was 35.27 ± 0.19%. On the other hand, saturated fatty acids (SFA) were more pronounced in CPO (38.44 ± 0.26%) than HPO (30.82 ± 0.55%). Based on nutrition indices, namely, atherogenicity index, thrombogenicity index, hypocholesterolemic/hypercholesterolemic (h/H) ratio, and PUFA/SFA ratio, HPO possessed higher health benefit than CPO. The oxidation status of CPO and HPO measured in terms of peroxide value, thiobarbituric acid reactive substances, anisidine value, and conjugated dienes indicated that higher primary oxidation products were present in CPO, whereas HPO exhibited more secondary oxidation compounds. Fourier transform infrared spectra further substantiated the presence of oxidation products in CPO and HPO. Liquid chromatography-mass spectrometry identification showed the enhanced levels of phospholipids and glycolipids in the ethanolic fraction of CPO. Overall, HPO with a higher yield was more beneficial in terms of health benefits than CPO.